Systematic evaluation of imaging techniques and baseline characteristics in patients with suspected vasculitis. (2022) - Koch, Vitali; Abt, Julia; Gruenewald, Leon D.; Eichler, Katrin; D'Angelo, Tommaso; Martin, Simon S.; Albrecht, Moritz H.; Thalhammer, Axel; Booz, Christian; Yel, Ibrahim; Bernatz, Simon; Mahmoudi, Scherwin; et al.
Abstract: Purpose: To assess the diagnostic value of different imaging modalities in distinguishing systemic vasculitis from other internal and immunological diseases. Methods: This retrospective study included 134 patients with suspected vasculitis who underwent ultrasound, magnetic resonance imaging (MRI), or 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) between 01/2010 and 01/2019, finally consisting of 70 individuals with vasculitis. The main study parameter was the confirmation of the diagnosis using one of the three different imaging modalities, with the adjudicated clinical and histopathological diagnosis as the gold standard. A secondary parameter was the morphological appearance of the vessel affected by vasculitis. Results: Patients with systemic vasculitis had myriad clinical manifestations with joint pain as the most common symptom. We found significant correlations between different imaging findings suggestive of vasculitis and the final adjudicated clinical diagnosis. In this context, on MRI, vessel wall thickening, edema, and diameter differed significantly between vasculitis and non-vasculitis groups ( p < 0.05). Ultrasound revealed different findings that may serve as red flags in identifying patients with vasculitis, such as vascular occlusion or halo sign ( p = 0.02 vs. non-vasculitis group). Interestingly, comparing maximal standardized uptake values from PET/CT examinations with vessel wall thickening or vessel diameter did not result in significant differences ( p > 0.05). Conclusions: We observed significant correlations between different imaging findings suggestive of vasculitis on ultrasound or MRI and the final adjudicated diagnosis. While ultrasound and MRI were considered suitable imaging methods for detecting and discriminating typical vascular changes, 18 F-FDG PET/CT requires careful timing and patient selection given its moderate diagnostic accuracy. Highlights: MRI and ultrasound provided significant correlations between findings suggestive of vasculitis and the final diagnosis. Careful selection of available imaging techniques is warranted considering the time course, location, and clinical history. Considering its moderate diagnostic power to distinguish tracer uptake, a holistic view of PET/CT findings is essential.